Pseudorandom bit generator based on non‐stationary logistic maps. Issue 2 (1st March 2016) - Liu, Lingfeng; Miao, Suoxia; Hu, Hanping; Deng, Yashuang
Abstract : Pseudorandom binary sequences play a significant role in many fields, such as error control coding, spread spectrum communications, and cryptography. In recent years, chaotic system is regarded as an important pseudorandom source in the design of pseudorandom bit generators (PRBGs). Among them, most are based on one or more fixed chaotic systems, and the generated binary sequences come to be stationary. However, these kinds of chaotic PRBGs can be attacked by reconstructing the phase space or using some statistical analysis methods. In this study, a scheme for chaotic PRBG based on non‐stationary logistic map is proposed. The authors design a dynamic algorithm to change the driven parameter sequence (not random) into a random‐like sequence. The variable parameters disrupt the phase space of the system, which can resist the phase space reconstruction attacks effectively. They prove that the non‐stationary logistic map is still chaotic under Wiggins' chaos definition. The numerical analysis shows that the generated binary sequences have good cryptographic properties and can pass the well‐known statistical tests. The authors' chaotic PRBG based on non‐stationary logistic map is a novel scheme in the design of PRBG, and is more secure than the PRBGs based on fixed chaotic systems.